HUBUNGAN USIA KEJANG DEMAM PERTAMA DAN RIWAYAT KELUARGA DENGAN KEJADIAN REKURENSI KEJANG DEMAM PADA ANAK DI RSUD ULIN BANJARMASIN - Habibie, Muhammad Rakha; Hidayah, Nurul; Huldani, Huldani; Hartoyo, Edi; Illiandri, Oski (Homeostasis, 2023)
The recurrence of febrile seizures is thought to be influenced by the occurrence of febrile seizures at a young age when the brain is still developing. In addition, the incidence of recurrences can also be influenced by hereditary factors from the family. The goal of this study is to explain the relationship between the patient age on the first febrile seizure and the family febrile seizure profile with its recurrence in children at Ulin Hospital, Banjarmasin. The research was conducted using a Cross Sectional Study with a total of 30 samples. The sampling technique was carried out by purposive sampling method. The data taken is secondary data from medical records at Ulin General Hospital, Banjarmasin. The data analysis are using chi-square and fischer as the test. The results showed that most of the patients caught on the first febrile seizure at >1 years old (53.3%), male (63.3%), with family febrile seizure history (63.3%) and had reccurence once (63.3%). The results of the data analysis showed that there was significant relationship (p=0.029) between the first febrile seizure age and recurrence events and also there was significant relationship (p=0.023) between family febrile seizure profile and recurrence events..